Plantwide Control and Simulation of Sulfur-Iodine Thermochemical Cycle Process for Hydrogen Production - Mohd, Noraini (Curtin University, 2018)
A PWC structure has developed for an industrial scale SITC plant. Based on the performance evaluation, it has been shown that the SITC plant developed via the proposed modified SOC structure can produce satisfactory performance – smooth and reliable operation. The SITC plant is capable of achieving a thermal efficiency of 69%, which is the highest attainable value so far. It is worth noting that the proposed SITC design is viable on the grounds of economic and controllability.